2010
DOI: 10.1111/j.1468-2958.2010.01396.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Koreans Are More Likely to Favor “Apology,” While Americans Are More Likely to Favor “Thank You”

Abstract: Two studies investigated whether apologies or thanks are preferred in asking favors in the United States and Korea, and how this relates to perceptions of reduction in positive and negative face threats. In the first study (n = 224), participants composed an e-mail message where a favor was asked. In the second (n = 807), participants completed questionnaires including a prototypical e-mail for the situation described in Study 1, as well as measures of negative and positive face threats. Findings showed that (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
3
29
1
Order By: Relevance
“…Indeed, Japanese students who were asked to think about a situation in which someone helped them spontaneously reported feeling sorry as well as gratitude (Kuranaga & Higuchi, ). Koreans are similar in this sense (Lee & Park, ). The interchangeable meaning of Japanese/Korean terms gratitude and indebtedness is thought to have originated from the Confucian concept of on (恩).…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, Japanese students who were asked to think about a situation in which someone helped them spontaneously reported feeling sorry as well as gratitude (Kuranaga & Higuchi, ). Koreans are similar in this sense (Lee & Park, ). The interchangeable meaning of Japanese/Korean terms gratitude and indebtedness is thought to have originated from the Confucian concept of on (恩).…”
Section: Introductionmentioning
confidence: 93%
“…In this case, when used on a Taiwan McDonald's Facebook site, they are referring to the site operators who speak for Taiwan McDonald's. Compared with the term "we", used by the American Facebook site operators to refer to themselves, the term "little" implies a value of the self-critical and self-improving orientation in Asian culture [41]. Lee and Park (2011) examined the usage of speech acts across different cultures, particularly in favor asking situations [41].…”
Section: Collectivism and Individualismmentioning
confidence: 99%
“…Compared with the term "we", used by the American Facebook site operators to refer to themselves, the term "little" implies a value of the self-critical and self-improving orientation in Asian culture [41]. Lee and Park (2011) examined the usage of speech acts across different cultures, particularly in favor asking situations [41]. They found that Confucianism, which assumes that the "self is fundamentally flawed and so modesty is emphasized, and good behavior toward others" (p. 128), might explain why Koreans more frequently include apologies in favor-asking messages [41].…”
Section: Collectivism and Individualismmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the view that people are rarely indifferent to how they are addressed (Tracy and Robles, 2013), it is perhaps of no surprise that recent studies have questioned the extent to which the opening and closing sections of emails should be regarded as simply customary (Lee and Park, 2011;Lee et al, 2012;Lorenzo-Dus and Bou-Franch, 2013). Indeed, subsequent research has exposed the pivotal role played by such linguistic objects in issues of: facework (Eckert and McConnell-Ginet, 2003); construction of professional identity (Scheyder, 2003); maintenance of workplace solidarity (Waldvogel, 2007); and, within student--teacher interactions, the execution of politeness strategies (Bjørge, 2007;Chejnová, 2014).…”
mentioning
confidence: 98%